PANDANGAN MASYARAKAT TERHADAP KEHADIRAN PERBANKAN SYARIAH DI INDONESIA - FATY RAHMARISA (LP2MTBM MAKARIOZ, 2020)
The development of sharia banking in general quite experienced a very significant increase, this is marked by the increasingrecognition of Islamic banks nationwide. Sharia banking in Indonesia is experiencing stable growth, although not as fast as inother countries such as Malaysia and the Middle East. This is due to various unhealthy criticisms to sharia financialinstitutions that are not experienced by conventional banking. As there is a kind of injustice in the treatment of sharia bankingwhere on the one hand is expected to make a profit, on the other hand is required to always make a profit sharing contract.To be required the cooperation of all the elements and components of Muslims in disseminating the understanding of theright sharia banking so that people can be more familiar with and understand about sharia banking and Islamic financialinstitutions.